Electrical characterization of InGaAs/InAlAs/InP HEMT with multi-finger gate. (December 2021) - He, Lijun; Zhao, Boyang; He, Chengyun; Xie, Zhiyang; Zhang, Jinsha; Chen, Weizhong
Abstract: InGaAs/InAlAs/InP high electron mobility transistor (HEMT) affords superb high-frequency operation. In this paper, the DC and RF characteristics of a novel InGaAs/InAlAs/InP HEMT with a multi-finger gate has been simulated using Silvaco Atlas at room temperature. The important feature of the device such as threshold voltage, drain current output characteristics, transconductance, cut-off frequency, and maximum oscillation frequency. The simulation results exhibit that characteristics can be well-improved, by using the multi-finger gate. Simulation results show a threshold voltage of −0.9 V, a crest of transconductance of 488 ms/mm, and the cut-off frequency and the maximum oscillation frequency are 853 GHz and 1.4 THz, respectively. These consequences permit us to verify that the device is intended for high-frequency applications.